Influence of ASEAN Centrality on Responses to the AUKUS Pact: A Comparative Study of Indonesia and the Philippines - Sianturi, Viona; Wiswayana, Wishnu (Universitas Cenderawasih, 2024)
This article aims to find answers to why two countries, despite sharing a high degree of similarity, may exhibit contrasting responses to a particular phenomenon. The Philippines and Indonesia share numerous similarities, encompassing geographical location, form of states, ideology, security, and economic conditions. Nevertheless, their reactions diverged when the AUKUS Defense Pact, aimed at bolstering security and stability in the Indo-Pacific, was established. Indonesia voiced concerns that the formation of the pact would potentially lead to an arms race in the region. Conversely, the Philippines responded positively by issuing verbal support for the establishment of AUKUS. Through the application of the most similar system design comparison method and Donald E Nuechterlein’s concept of National Interest analysis, this article concludes that the Philippines and Indonesia adopt distinct approaches and harbor different interests in the preservation of regional stability. Indonesia has interest in prioritizing the principle of ASEAN centrality through the application of the ASEAN Outlook on Indo-Pacific. On the other hand, the Philippines considers it crucial to involve their traditional defense partners, the United States and Australia, in upholding regional security. KEYWORDS ASEAN Centrality; AUKUS; Indonesia; National Interest; Philippines